The Capitalization of the Land Tax - Hayes, H. G. (Quarterly Journal of Economics, 1920)
The Capitalization of the Land Tax Get access H. G. Hayes H. G. Hayes Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 34, Issue 2, February 1920, Pages 373–380, https://doi.org/10.2307/1882371 Published: 01 February 1920